SPEECH FUNCTION ANALYSIS IN PRESIDENT PRABOWO SUBIANTO’ INTERVIEW WITH NAJWA SHIHAB - Natalia Murni Br Situmorang; Bertaria Sohnata Hutauruk; Melda Veby Ristella Munthe (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the speech functions used by President Prabowo Subianto and Najwa Shihab, particularly how the president conveys information and influences public perception. This study uses qualitative descriptive research, namely documentation analysis. Data were taken from the transcript of an interview between President Prabowo Subianto and Najwa Shihab during the "President Answers" program on Najwa Shihab's YouTube account on April 6, 2025. The analysis focused on speech functions based on Haliday's (2014) theory: statement, command, question, and offer. The results showed that the most frequently occurring speech function was the statement, with 294 utterances (74.73%). The second most frequently occurring speech function was the question, with 52 utterances (18%). Next came the command speech function with 23 utterances (6.2%). Finally, the least frequently occurring speech function was the offer, with 2 utterances (0.5%). This research concludes that President Prabowo's use of speech function in the interview was strategic, namely, in addition to reporting information or facts, it also formed a narrative of President Prabowo's leadership image.